Audio Afirmasi Untuk Membentuk Harga Diri Positif Individu - Dinna Zebua; Anisa Sitepu; Arie Nasution; Muhammad Dinata (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
This research was conducted to examine more deeply related to audio affirmations. There has been no research that examines audio affirmations, especially in shaping one's self-esteem. Furthermore, this study was conducted to answer how the use of affirmation audio can make positive self-esteem, how affirmation audio works can make individual positive self-esteem and see the efficiency of using positive affirmation audio. This type of research is qualitative research. The type of literature research found that positive affirmation audio works through the subconscious mind and then passes through a system called the Reticular Activating System (RAS). Especially when the affirmation audio is heard when the brain waves are in theta state. So that individuals have more time to process positive words into their subconscious and remember them compared to general affirmation techniques that have to think of appropriate sentences in the process of giving affirmations. The subconscious mind continues to repeat the positive sentence so that the sel view can be understood more positively consciously. Keywords: Positive affirmations; audio affirmations; self-esteem